The incidence of hepatocellular carcinoma and clearance of hepatitis B surface for CHB patients in the indeterminate phase: a systematic review and meta-analysis - Liu, Min; Zhao, Taixue; Zhang, Yuting; Zhang, A-Mei; Geng, Jiawei; Xia, Xueshan (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Nearly 30%-40% of patients with chronic hepatitis B do not fall into any of the traditional natural history and thus are classified as indeterminate. However, it is unclear whether patients in the indeterminate phase (IP) are at a higher risk for HCC compared to the defined phases (DP) and would benefit from antiviral therapy. We performed a systematic review and meta-analysis of HCC incidence and HBsAg clearance among patients in the IP versus DP. We defined the clinical phases as per the AASLD 2018 hepatitis B guidance. We searched PubMed, Embase, Medline, and Web of Science for relevant studies that reported HCC incidence or HBsAg clearance in IP versus DP patients published between January 2007 and March 2023. Annual HCC incidence and HBsAg clearance rates were pooled using a random/common effects model. We analyzed data from 14 studies, comprising 798 IP patients and 10725 DP patients. The pooled annual HCC incidence of 2.54 cases per 1000 person-years (95% CI, 1.14-4.39) and HBsAg clearance rate was 12.36 cases per 1000 person-years (95% CI, 10.70-14.13) for the IP patients, respectively. IP patients were associated with significantly higher HCC incidence risk (RR=1.64, 95% CI, 1.34-2.00) and slightly lower annual HBsAg clearance rate (RR=0.83, 95% CI, 0.70-0.99) than the DP patients. In addition, HBeAg negative IP patients (2.31%; 95% CI, 0.87-4.45) showed a significantly higher HCC incidence than those HBeAg positive (0.00%; 95% CI, 0.00-0.99) (P＜0.001). The Asia Pacific region IP patients (4.30%; 95% CI, 2.07-7.27) were also associated with a higher HCC incidence versus Europe (0.05%; 95% CI, 0.00-1.39) (P＜0.001). However, there were no significant differences between different strategies (treated vs. untreated: 2.56%; 95% CI, 1.01-4.63 vs. 1.61%; 95%CI, 0.00-5.81, P=0.09), heterogeneity was substantial across the studies (I 2 =89%). The systematic review and meta-analysis showed a high HCC incidence and low HBsAg clearance among patients in the IP, especially for those HBeAg negative and Asian populations. We emphasize future multicenter prospective cohort studies or randomized trials are needed to verify if expanding antiviral therapy for patients in the IP is associated with reduced HCC risk or good treatment outcomes.